2008
DOI: 10.1111/j.1744-7348.2008.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae to sweet potato weevil Cylas puncticollis and effects on fecundity and egg viability

Abstract: The virulence of eight isolates of Metarhizium anisopliae and four isolates of Beauveria bassiana (Ascomycota: Hypocreales) to adult Cylas puncticollis (Coleoptera: Curculionidae) was tested in the laboratory. Insects were sprayed with a standard concentration of 1.0 × 107 conidia mL−1 using Burgerjon’s spray tower. All the isolates tested were pathogenic to C. puncticollis. Mortality varied between 77.5% and 84.2% with isolates of B. bassiana and between 62.5% and 89.2% with isolates of M. anisopliae, 26 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 22 publications
2
43
0
4
Order By: Relevance
“…Results showed that Metarhizium brunneum with spinosad (insecticide) and Beauveria bassiana with spinosad caused 100% adult weevil mortality at 48 hours after treatment, while Metarhizium brunneum and Beauveria bassiana alone required 168 to 192 hours after treatment to cause 100% mortality of C formicarius. However, Ondiaka et al 2008 determined the effect of Beauveria bassiana and Metarhizium anisopliae on adult Cylas puncticollis and fecundity and viability of female Cylas puncticollis eggs and found that, spraying of Beauveria bassiana or Metarhizium anisopliae caused adult mortality between 62.5% and 89.2%. In addition, adult females, treated with both fungal species, laid less eggs compared to control, suggesting that the fungi can significantly reduce fecundity and egg viability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that Metarhizium brunneum with spinosad (insecticide) and Beauveria bassiana with spinosad caused 100% adult weevil mortality at 48 hours after treatment, while Metarhizium brunneum and Beauveria bassiana alone required 168 to 192 hours after treatment to cause 100% mortality of C formicarius. However, Ondiaka et al 2008 determined the effect of Beauveria bassiana and Metarhizium anisopliae on adult Cylas puncticollis and fecundity and viability of female Cylas puncticollis eggs and found that, spraying of Beauveria bassiana or Metarhizium anisopliae caused adult mortality between 62.5% and 89.2%. In addition, adult females, treated with both fungal species, laid less eggs compared to control, suggesting that the fungi can significantly reduce fecundity and egg viability.…”
Section: Methodsmentioning
confidence: 99%
“…Here the fungus proliferates throughout the body of the insect and produces toxins, draining the insect of nutrients and eventually killing it. Beauveria bassiana is considered a virulent pathogen against the banana weevil Cosmopolites sordidus (Coleoptera: Curculionidae) (Ondiaka et al 2008) and has also been used successfully in the control of the coffee borer (Smit et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results to this study were observed in the reproductive output of Tutta absoluta (Pires et al, 2008), using doses of 10 7 conidia mL -1 of M. anisopliae and Diuraphis noxia (Wang and Knudsen, 1993) using B. bassiana. Other studies have shown positive results on this topic, for example Cylas puncticollis (Ondiaka et al, 2008), Anoplophora glabripennis (Hajek et al, 2008), Megalurothrips sjostedti (Ekesi and Maniania, 2000), among others.…”
Section: Virulencementioning
confidence: 99%
“…Likewise, inoculating directly on eggs of Bemisia argentifolii with Verticillium lecanii Zimmermann, this showed no pathogenic effects, however all other developmental stages of the species were affected by the pathogen (Gindin et al, 2000). On the other hand, other studies have shown effects on egg fertility of survival females infected by M. anisopliae, as Nymph I 37.5 ± 4.8aA 50.0 ± 10.8aA 62.5 ± 21.7aA 52.5 ± 11.1abA 65.0 ± 8.7aA Nymph II 25.0 ± 5.0aA 52.5 ± 2.5aABC 70.0 ± 12.2aBC 42.5 ± 2.5aAB 80.0 ± 10.8aC Nymph III 27.5 ± 11.1aA 40.0 ± 5.8aAB 52.5 ± 12.5aABC 85.0 ± 6.5cC 80.0 ± 8.2aBC Adult 12.5 ± 4.8aA 50.0 ± 12.9aAB 50.0 ± 10.8aAB 80.0 ± 7.1bcB 87.5 ± 6.3aB in the case of Megalurothrips sjostedti at concentrations of 10 6 to 10 8 conidia mL -1 (Ekesi and Maniania, 2000) and Cylas puncticollis at concentrations from 1 × 10 6 to 3.0 × 10 7 conidia mL -1 (Ondiaka et al, 2008).…”
Section: Virulencementioning
confidence: 99%
“…Hal ini disebabkan senyawa insektisida kimia yang diaplikasikan ke permukaan tanaman tidak mampu menjangkau larva yang berada di dalam umbi. Berbagai upaya untuk menanggulangi C. formicarius terus dikembangkan (Tarafdar & Sarkar 2006;Foglie, 2007;Korada et al, 2010;Reddy et al, 2014;Hue & Low, 2015), salah satunya adalah upaya pengendalian hayati menggunakan jamur entomopatogen (Gindin et al, 2006;Ondiaka et al, 2008;Shams et al, 2011;Khosravi et al, 2015).…”
Section: Pendahuluanunclassified